If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3y + -8) + 2(2y + 8) = 0 Reorder the terms: -5(-8 + 3y) + 2(2y + 8) = 0 (-8 * -5 + 3y * -5) + 2(2y + 8) = 0 (40 + -15y) + 2(2y + 8) = 0 Reorder the terms: 40 + -15y + 2(8 + 2y) = 0 40 + -15y + (8 * 2 + 2y * 2) = 0 40 + -15y + (16 + 4y) = 0 Reorder the terms: 40 + 16 + -15y + 4y = 0 Combine like terms: 40 + 16 = 56 56 + -15y + 4y = 0 Combine like terms: -15y + 4y = -11y 56 + -11y = 0 Solving 56 + -11y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -11y = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -11y = 0 + -56 -11y = 0 + -56 Combine like terms: 0 + -56 = -56 -11y = -56 Divide each side by '-11'. y = 5.090909091 Simplifying y = 5.090909091
| 6(5+3x)=48 | | 4a-7=5 | | 4x+3/7+1=7x+1/2-2 | | 4x+10=5x+8 | | a/4+4/8=8a/7+7/3 | | 4.7-2.5+2.7x=12.8-1.6x | | 2+5y/8=2/8+5y | | 11=2b | | -9z-2z=2z-1+7z | | 4-3z/5=7-3z/4 | | 4+6x=2x+16 | | 10-3x-6-7x=6 | | 2.5-x=2+1.5x | | (3v-4)(4v-6)= | | x+2=-10+3x | | -4(4y+5)-11=-8(y+5)+4y | | -9(v+2)+3v+7=8v+6 | | 5x+4=4x+12 | | 9+4(x-2)=6x | | 2(2x+2)=3(x-3) | | -3(5-4k)=6k+15 | | -2x-5(x+6)=-2(3x+9) | | 6x^2+12x-210=0 | | 4x+2=5x-10 | | 7x+4=.125(8x-40) | | 9+6x=7x-1 | | 2x^2+4= | | 12-5(x-1)=-3x+3(2-x) | | 15x+9(9-x)=3x-18 | | 5+2x=3x+5 | | 13(y-4)=3(4y+6)-70 | | 7x+2+x=2 |